Development of a novel carboxamide-based off–on switch fluorescence sensor: Hg2+, Zn2+ and Cd2+. (1st July 2020) - Kiani, Mahsa; Bagherzadeh, Mojtaba; Meghdadi, Soraia; Rabiee, Navid; Abbasi, Alireza; Schenk-Joß, Kurt; Tahriri, Mohammadreza; Tayebi, Lobat; Webster, Thomas J.
Abstract : Here, the carboxamide ligand N -(thiazole-2-yl) picolinamide (L ) was synthesized in an ionic liquid tetrabutylammonium bromide (TBAB) as the benign reaction medium. Abstract : Here, the carboxamide ligand N -(thiazole-2-yl) picolinamide (L ) was synthesized in an ionic liquid tetrabutylammonium bromide (TBAB) as the benign reaction medium. The sensitivity of L towards different metal-ions was investigated, and a comprehensive, logical optical investigation was conducted for the IIB transition metal ions, Hg 2+, Cd 2+ and Zn 2+, based on off–on switch sensor protocols. In the absence of these metal ions, L showed weak emission only, but fluorescence intensity increased considerably upon their addition to a sensitivity range of 10 −6 M. This phenomenon was enhanced significantly in the presence of Zn 2+ compared to other metal ions, likely due to the coordination of metallic ions to the L, which led to the chelation-enhanced fluorescence (CHEF) effect. To prove these results, several characterization studies were conducted: a single crystal from the metal–ligand complex was prepared, followed by conduction of X-ray single crystal analysis from the Zn-complex (2 ) and Cd-complex (3 ), and conducting spectral analysis from the Zn 2+, Hg 2+ and Cd 2+ complexes. These complexes and also the ligand showed very low toxicity on the PC12 cell line suggesting their promise for a wide range of future medical applications.